Nonwoven-film composite insulation material thermoforming process
By employing plasma treatment, corona treatment, and flame retardant synergist coating during the hot pressing process of nonwoven fabric-film composite insulation material, and dynamically matching the temperature and pressure fields to regulate the arrangement of nanoparticles, a dense interpenetrating network structure is formed. This solves the problems of decreased interfacial bonding force and deterioration of dielectric properties, achieving a comprehensive performance of high insulation, toughness, and heat resistance in the material.
Patent Information
- Application Number
- CN202511299929.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-09-12
AI Technical Summary
During the hot pressing process of nonwoven fabric-film composite insulation materials, there are problems such as decreased interfacial bonding force, deterioration of dielectric properties, and crack propagation caused by nanoparticle agglomeration, which affect the long-term service reliability of the materials.
By constructing a nanoscale anchoring structure through plasma treatment and corona treatment, combined with the coating structure of flame retardant synergists and segmented pressure relief technology, the temperature field and pressure field are dynamically matched to regulate the arrangement of nanoparticles in three-dimensional space, forming a dense interpenetrating network structure, thereby achieving chemical bonding and mechanical interlocking between nonwoven fabric and film.
It improves the interlayer bonding strength, ensures the dielectric stability of the composite system, inhibits crack propagation, enhances the service reliability of the material under extreme conditions, and possesses comprehensive properties of high insulation, toughness and heat resistance.
Smart Images

Figure SMS_13
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite insulation materials technology, specifically to the hot pressing process for nonwoven fabric-film composite insulation materials. Background Technology
[0002] Insulating composite materials are functional materials made by adding specific fillers and reinforcing fibers to a thermosetting resin matrix. Their core characteristics include the use of a composite system of bisphenol A type epoxy resin and azole ketone ring-modified epoxy resin, and a filler system with a micron / nano-scale bimodal distribution.
[0003] Currently, due to the multiple process coupling effects in the hot pressing process of nonwoven fabric-film composite insulation materials, the temperature and pressure fields applied by the hot pressing equipment cannot be matched with the deformation state of the substrate in real time when controlling the bonding of the composite interface. When uneven local temperature distribution or abnormal pressure fluctuations occur during the hot pressing stage, microbubble defects will be generated at the interface, resulting in a decrease in the bonding force between the composite layers. At the same time, in the flame retardant migration inhibition stage, the molecular diffusion behavior of the flame retardant during the hot pressing process cannot be dynamically monitored. When the concentration of flame retardant migrating to the film side exceeds the critical threshold, it will cause the dielectric properties to deteriorate, and this migration phenomenon cannot be corrected in real time by process parameters. In the dispersion control of the nano-reinforcing phase, due to the dynamic change of resin viscosity during the hot pressing curing stage, it is impossible to regulate the directional arrangement of nanoparticles in three-dimensional space, which leads to the formation of stress concentration points in the interface region by particle agglomerates, further inducing crack propagation in the composite material under high temperature environment, ultimately affecting the long-term service reliability of the insulation material.
[0004] Therefore, a hot-pressing process for nonwoven fabric-film composite insulation materials is proposed to solve the above problems. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a hot-pressing molding process for nonwoven fabric-film composite insulation materials. The hot-pressing molding process provided by this invention solves the problem mentioned in the background technology that the composite material will develop cracks at high temperatures, ultimately affecting the long-term service reliability of the insulation material.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a hot-pressing molding process for non-woven fabric-film composite insulating materials, comprising the following steps:
[0007] Step 1: Substrate pretreatment, selecting polyester nonwoven fabric and polyimide film, wherein the basis weight of the nonwoven fabric is 30-50 g / m². 2 The thickness is 0.1-0.3mm, the film thickness is 12-25μm, and the non-woven fabric is subjected to plasma hydrophilization treatment with a treatment power of 300-800W and a time of 30-90s.
[0008] Step 2: Flame retardant impregnation. Immerse the pretreated nonwoven fabric in flame retardant liquid at a temperature of 40-60℃ for 5-15 minutes. After removal, dry at 80-100℃.
[0009] Step 3: Surface treatment of the film. The polyimide film is subjected to corona treatment on one side, and the surface tension is controlled to be 50-56 mN / m.
[0010] Step 4: Preparation of the composite adhesive solution. Prepare the composite adhesive solution according to the following mass percentages: modified epoxy resin 36.4%-54.5%, cyanate ester resin 18.2%-27.3%, nano-alumina 4.5%-9.1%, flame retardant synergist 2.7%-7.3%, silane coupling agent 0.5%-1.8%, with the remainder being solvent to achieve the coating viscosity. The solvent is selected from water, alcohol ethers, or ketones, accounting for 15-20% of the total adhesive solution mass.
[0011] Step 5: Coating and laminating. Apply the laminating adhesive to the surface of the corona-treated film, with a coating amount of 8-15 g / m². 2 It is then laminated with flame-retardant nonwoven fabric by roller pressing, with a roller pressing pressure of 0.3-0.8MPa;
[0012] Step 6: Hot pressing. Place the composite blank in a hot press and cure it in stages: first stage 80-100℃ / 0.5-1h, second stage 120-140℃ / 1-2h, third stage 160-180℃ / 2-3h, and maintain the pressure at 5-10MPa throughout the process.
[0013] Preferably, the plasma treatment in step one is carried out under a nitrogen atmosphere with a gas flow rate of 20-50 L / min. After treatment, a nanoscale pit structure is formed on the surface of the nonwoven fabric, with a pit depth of 50-200 nm and a density of 10. 5 -10 6 pcs / cm 2 .
[0014] Preferably, the flame retardant liquid in step two is composed of the following components by mass percentage:
[0015] Ammonium polyphosphate: 15-25%;
[0016] Melamine cyanurate: 8-15%;
[0017] Zinc borate: 3-8%;
[0018] Dispersant, polyvinyl butyral: 0.5-1.5%;
[0019] The remaining amount is 50.5-73.5% deionized water;
[0020] The flame retardant liquid must meet the following requirements: deionized water conductivity ≤ 0.1 μS / cm, total metal ion content ≤ 50 ppb;
[0021] The pH value of the flame retardant liquid is adjusted to 6.5-7.5, and the viscosity is controlled to 25-50 mPa·s.
[0022] Preferably, the modified epoxy resin in step four is a mixture of bisphenol A type epoxy resin and phosphorus-containing epoxy resin, with a mixing mass ratio of 7:3-5:5 and an epoxy equivalent of 180-220 g / eq.
[0023] The nano-alumina is a γ-phase. Particle size 20-50nm, specific surface area 80-150m² 2 / g, surface modified with silane coupling agent KH-550.
[0024] Preferably, the flame retardant synergist in step four is prepared by the following method:
[0025] Waste ceramic powder was ball-milled to a particle size of 1-5 μm and mixed with aluminum hydroxide at a mass ratio of 3:1.
[0026] Placed in a plasma reactor, argon gas is introduced to achieve a pressure of [insert pressure here]. Pa, processed at 200-500W power for 10-30 minutes;
[0027] The treated powder was immersed in 5% silica sol for 10 minutes and then dried to obtain a coated flame retardant synergist.
[0028] Preferably, step four, the preparation of the composite adhesive solution, specifically includes:
[0029] The modified epoxy resin and cyanate ester resin were stirred and mixed at 200-400 r / min at 50-60℃ for 20-40 min.
[0030] Add silane coupling agent and nano-alumina, and ultrasonically disperse at 800-1200W for 15-30 minutes;
[0031] Add flame retardant synergist, heat to 70-80℃ and continue stirring for 30-60 minutes;
[0032] Cool the temperature down to below 40℃, add 1-3 parts of the curing agent dicyandiamide and mix well;
[0033] Add the selected solvent and adjust the viscosity of the adhesive to 25-50 mPa·s at 25°C.
[0034] Preferably, the roll lamination in step five uses a three-roller coating machine, wherein:
[0035] The gap between the coating roller and the metering roller is 0.05-0.15mm, the temperature of the composite pressure roller is set to 50-70℃, the composite speed is 2-5m / min, and the composite material is immediately placed in a 60-80℃ hot air zone for pre-curing for 1-3min.
[0036] Preferably, the hot pressing process in step six employs a segmented pressure relief technique:
[0037] 10 minutes before the end of the first stage of heating, the pressure is released to 2-3 MPa and held for 10 minutes.
[0038] 15 minutes before the end of the second stage, the pressure is released to 1-2 MPa and maintained for 15 minutes.
[0039] 20 minutes before the end of the third stage, the pressure was released to atmospheric pressure and maintained until the end.
[0040] Preferably, a post-processing step is added after hot pressing in step six:
[0041] Place the molding material in a vacuum oven and treat it at 120-140℃ for 2-4 hours, with a vacuum degree ≤ Pa;
[0042] Immediately after treatment, immerse the sample in a coolant containing 0.5% fluorocarbon surfactant to cool it rapidly to room temperature.
[0043] Preferably, an ultrasonic vibration device is added between the coating roller and the metering roller, and this device satisfies the following:
[0044] The vibration frequency is 20-40 kHz, the amplitude is 5-15 μm, and the vibration direction forms an angle of 45°-90° with the coating direction. Ultrasonic vibration is continuously applied during the coating process, and the vibration energy density is controlled at 0.5-2.0 J / cm². 2 ·s.
[0045] (III) Beneficial Effects
[0046] Compared with the prior art, the present invention provides a hot pressing process for nonwoven fabric-film composite insulation materials, which has the following advantages:
[0047] 1. In this invention, by synergistically controlling the temperature field and pressure field during the hot pressing stage to dynamically match the deformation behavior of the substrate, the interfacial microbubble defects caused by uneven local temperature distribution and pressure fluctuations are eliminated, thereby achieving the fusion of the nonwoven fabric and film interface and improving the interlayer bonding strength. At the same time, by utilizing the coating structure of the flame retardant synergist and the pH control of the adhesive, the abnormal migration of flame retardant molecules during the hot pressing process is dynamically suppressed, ensuring the long-term stability of the dielectric properties of the composite system and avoiding the problem of insulation performance degradation caused by flame retardant concentration imbalance.
[0048] 2. In this invention, by utilizing the synergistic surface activation effect of plasma treatment and corona treatment, a nanoscale anchoring structure is constructed on the surface of the nonwoven fabric, and the surface polarity of the film is enhanced, so that the composite adhesive forms a dual effect of chemical bonding and mechanical interlocking at the substrate interface; through the surface modification of nanoparticles and directional ultrasonic dispersion technology, the arrangement of the reinforcing phase in three-dimensional space is controlled, the stress concentration phenomenon caused by particle agglomeration is eliminated, the crack propagation path is blocked in the high temperature environment, and the service reliability of the composite insulation material under extreme working conditions is improved.
[0049] 3. In this invention, the coupling effect of segmented pressure relief hot pressing technology and vacuum post-treatment process is adopted to release residual stress at the interface in stages and eliminate micro-pores, so that the adhesive layer forms a dense interpenetrating network structure during the curing process; combined with the resin micro-phase transformation induced by rapid cooling treatment, the mechanical interlocking and chemical cross-linking density of the composite interface are strengthened, realizing the full-domain integrated combination of non-woven fabric-film-adhesive layer sandwich structure, ensuring that the material has the comprehensive performance advantages of high insulation, toughness and heat resistance. Detailed Implementation
[0050] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0051] Example 1: Hot pressing process for nonwoven fabric-film composite insulation material, including the following steps:
[0052] Step 1: Substrate pretreatment, selecting polyester nonwoven fabric and polyimide film, wherein the nonwoven fabric basis weight is 30g / m². 2 The nonwoven fabric is subjected to plasma hydrophilization treatment with a thickness of 0.1 mm and a film thickness of 12 μm. The treatment power is 300 W and the time is 30 s.
[0053] Step 2: Flame retardant impregnation. Immerse the pretreated nonwoven fabric in flame retardant liquid at 40°C for 5 minutes. After removal, dry at 80°C.
[0054] Step 3: Surface treatment of the film. The polyimide film is subjected to corona treatment on one side, and the surface tension is controlled to be 50mN / m.
[0055] Step 4: Preparation of the composite adhesive solution. The composite adhesive solution is prepared according to the following weight percentages: modified epoxy resin 36.4%, cyanate ester resin 27.3%, nano-alumina 9.1%, flame retardant synergist 7.3%, silane coupling agent 1.8%, with the remainder being solvent to achieve the desired coating viscosity. The solvent is selected from water, alcohol ethers, or ketones, preferably deionized water, accounting for 18.1% of the total adhesive solution mass.
[0056] Step 5: Coating and Lamination. Apply the laminating adhesive to the corona-treated film surface at a coating weight of 8 g / m². 2 It is then laminated with flame-retardant nonwoven fabric by roller pressing at a pressure of 0.3 MPa.
[0057] Step 6: Hot pressing. Place the composite blank in a hot press and cure it in stages: first stage 80℃ / 0.5h, second stage 120℃ / 1h, third stage 160℃ / 2h, with the pressure maintained at 5MPa throughout.
[0058] The plasma treatment in step one was carried out under a nitrogen atmosphere with a gas flow rate of 20 L / min. After treatment, a nanoscale pit structure was formed on the surface of the nonwoven fabric, with a pit depth of 50 nm and a density of 10. 5 pcs / cm 2 .
[0059] The flame retardant liquid in step two is composed of the following components by mass percentage:
[0060] Ammonium polyphosphate: 15%;
[0061] Melamine cyanurate: 8%;
[0062] Zinc borate: 3%;
[0063] Dispersant, polyvinyl butyral: 1.5%;
[0064] The remaining volume is 72.5% deionized water;
[0065] Flame retardant liquids must meet the following requirements: deionized water conductivity ≤ 0.1 μS / cm, total metal ion content ≤ 50 ppb;
[0066] The pH of the flame retardant liquid was adjusted to 6.5, and the viscosity was controlled to 25 mPa·s.
[0067] The modified epoxy resin in step four is a mixture of bisphenol A type epoxy resin and phosphorus-containing epoxy resin, with a mixing mass ratio of 7:3 and an epoxy equivalent of 180 g / eq.
[0068] Nano-alumina is a γ phase Particle size 20nm, specific surface area 80m² 2 / g, surface modified with silane coupling agent KH-550.
[0069] The flame retardant synergist in step four is prepared by the following method:
[0070] Waste ceramic micro powder was ball-milled to a particle size of 1μm and mixed with aluminum hydroxide at a mass ratio of 3:1.
[0071] Placed in a plasma reactor, argon gas is introduced to achieve a pressure of [insert pressure here]. Pa, processed at 200W power for 10 minutes;
[0072] The treated powder was immersed in 5% silica sol for 10 minutes and then dried to obtain a coated flame retardant synergist.
[0073] Step four, the preparation of the composite adhesive solution, specifically includes:
[0074] The modified epoxy resin and cyanate ester resin were stirred and mixed at 200 r / min at 50℃ for 20 min.
[0075] Add silane coupling agent and nano-alumina, and ultrasonically disperse for 15 minutes at 800W.
[0076] Add flame retardant synergist, heat to 70℃ and continue stirring for 30 minutes;
[0077] Cool the temperature down to below 40°C, add 1 part of the curing agent dicyandiamide and mix well;
[0078] Add the selected solvent and adjust the viscosity of the adhesive to 25 mPa·s at 25°C.
[0079] Step five, roll lamination, uses a three-roll coating machine, wherein:
[0080] The gap between the coating roller and the metering roller is 0.05 mm, the temperature of the composite pressure roller is set to 50℃, the composite speed is 2 m / min, and the composite material is immediately placed in a 60℃ hot air zone for pre-curing for 1 min after composite.
[0081] Step six, hot pressing, employs a segmented pressure relief technique:
[0082] The pressure was released to 2 MPa 10 minutes before the end of the first stage of heating and held for 10 minutes.
[0083] 15 minutes before the end of the second stage, the pressure is released to 1 MPa and maintained for 15 minutes.
[0084] 20 minutes before the end of the third stage, the pressure was released to atmospheric pressure and maintained until the end.
[0085] A post-processing step is added after hot pressing in step six:
[0086] The molding material was placed in a vacuum oven and treated at 120°C for 2 hours, with a vacuum degree ≤ Pa;
[0087] Immediately after treatment, immerse the sample in a coolant containing 0.5% fluorocarbon surfactant to cool it rapidly to room temperature.
[0088] An ultrasonic vibration device is added between the coating roller and the metering roller. This device satisfies the following requirements:
[0089] The vibration frequency was 20 kHz, the amplitude was 5 μm, and the vibration direction was at a 45° angle to the coating direction. The ultrasonic vibration was continuously applied during the coating process, and the vibration energy density was controlled at 0.5 J / cm². 2 ·s.
[0090] Example 2: Hot pressing molding process for non-woven fabric-film composite insulation material, including the following steps:
[0091] Step 1: Substrate pretreatment, selecting polyester nonwoven fabric and polyimide film, wherein the nonwoven fabric has a basis weight of 40 g / m². 2 The nonwoven fabric is subjected to plasma hydrophilization treatment with a thickness of 0.2 mm and a film thickness of 20 μm. The treatment power is 500 W and the time is 60 s.
[0092] Step 2: Flame retardant impregnation. Immerse the pretreated nonwoven fabric in flame retardant liquid at a temperature of 50°C for 10 minutes. After removal, dry at 90°C.
[0093] Step 3: Surface treatment of the film. The polyimide film is subjected to corona treatment on one side, and the surface tension is controlled to be 53mN / m.
[0094] Step 4: Preparation of composite adhesive solution. The composite adhesive solution is prepared according to the following mass percentages: modified epoxy resin 45.5%, cyanate ester resin 22.7%, nano alumina 6.8%, flame retardant synergist 5.0%, silane coupling agent 1.0%, with the remainder being solvent to achieve the coating viscosity. The solvent is selected from water, alcohol ethers, or ketones, preferably deionized water, accounting for 19.0% of the total mass of the adhesive solution.
[0095] Step 5: Coating and laminating. Apply the laminating adhesive to the corona-treated film surface at a coating weight of 12 g / m². 2 It is then laminated with flame-retardant nonwoven fabric by roller pressing at a pressure of 0.5 MPa.
[0096] Step 6: Hot pressing. Place the composite blank in a hot press and cure it in stages: first stage 90℃ / 1.0h, second stage 130℃ / 1.5h, third stage 170℃ / 2.5h, with the pressure maintained at 8MPa throughout.
[0097] The plasma treatment in step one was carried out under a nitrogen atmosphere with a gas flow rate of 35 L / min. After treatment, a nanoscale pit structure was formed on the surface of the nonwoven fabric, with a pit depth of 150 nm and a density of 10.5 pcs / cm 2 .
[0098] The flame retardant liquid in step two is composed of the following components by mass percentage:
[0099] Ammonium polyphosphate: 20%;
[0100] Melamine cyanurate: 10%;
[0101] Zinc borate: 5%;
[0102] Dispersant, polyvinyl butyral: 1.0%;
[0103] The remaining volume is 64.0% deionized water;
[0104] Flame retardant liquids must meet the following requirements: deionized water conductivity ≤ 0.1 μS / cm, total metal ion content ≤ 50 ppb;
[0105] The pH of the flame retardant liquid was adjusted to 7.0, and the viscosity was controlled to 35 mPa·s.
[0106] The modified epoxy resin in step four is a mixture of bisphenol A type epoxy resin and phosphorus-containing epoxy resin, with a mixing mass ratio of 3:2 and an epoxy equivalent of 200 g / eq.
[0107] Nano-alumina is a γ phase Particle size 35nm, specific surface area 120m² 2 / g, surface modified with silane coupling agent KH-550.
[0108] The flame retardant synergist in step four is prepared by the following method:
[0109] Waste ceramic powder was ball-milled to a particle size of 3μm and then mixed with aluminum hydroxide at a mass ratio of 3:1.
[0110] Placed in a plasma reactor, argon gas is introduced to achieve a pressure of [insert pressure here]. Pa, processed at 400W power for 20 minutes;
[0111] The treated powder was immersed in 5% silica sol for 10 minutes and then dried to obtain a coated flame retardant synergist.
[0112] Step four, the preparation of the composite adhesive solution, specifically includes:
[0113] The modified epoxy resin and cyanate ester resin were stirred and mixed at 300 r / min at 55℃ for 30 min.
[0114] Add silane coupling agent and nano-alumina, and ultrasonically disperse for 20 minutes at 1000W.
[0115] Add flame retardant synergist, heat to 75℃ and continue stirring for 45 minutes;
[0116] Cool the temperature down to below 40℃, add 2 parts of the curing agent dicyandiamide and mix well;
[0117] Add the selected solvent and adjust the viscosity of the adhesive to 40 mPa·s at 25°C.
[0118] Step five, roll lamination, uses a three-roll coating machine, wherein:
[0119] The gap between the coating roller and the metering roller is 0.10 mm, the temperature of the composite pressure roller is set to 60℃, the composite speed is 3 m / min, and the composite material is immediately placed in a 70℃ hot air zone for pre-curing for 2 min after lamination.
[0120] Step six, hot pressing, employs a segmented pressure relief technique:
[0121] Ten minutes before the end of the first stage of heating, the pressure was released to 2.5 MPa and held for 10 minutes.
[0122] The pressure was released to 1.5 MPa 15 minutes before the end of the second stage and held for 15 minutes.
[0123] 20 minutes before the end of the third stage, the pressure was released to atmospheric pressure and maintained until the end.
[0124] A post-processing step is added after hot pressing in step six:
[0125] The molding material was placed in a vacuum oven and treated at 130°C for 3 hours, with a vacuum degree ≤ Pa;
[0126] Immediately after treatment, immerse the sample in a coolant containing 0.5% fluorocarbon surfactant to cool it rapidly to room temperature.
[0127] An ultrasonic vibration device is added between the coating roller and the metering roller. This device satisfies the following requirements:
[0128] The vibration frequency was 30 kHz, the amplitude was 10 μm, and the vibration direction was at a 60° angle to the coating direction. The ultrasonic vibration was continuously applied during the coating process, and the vibration energy density was controlled at 1.0 J / cm². 2 ·s.
[0129] Example 3: Hot pressing process for nonwoven fabric-film composite insulation material. Step 1: Substrate pretreatment, selecting polyester nonwoven fabric and polyimide film, wherein the nonwoven fabric basis weight is 50g / m². 2 The nonwoven fabric is subjected to plasma hydrophilization treatment with a thickness of 0.3 mm and a film thickness of 25 μm. The treatment power is 800 W and the time is 90 s.
[0130] Step 2: Flame retardant impregnation. Immerse the pretreated nonwoven fabric in flame retardant liquid at a temperature of 60°C for 15 minutes. After removal, dry at 100°C.
[0131] Step 3: Surface treatment of the film. The polyimide film is subjected to corona treatment on one side, and the surface tension is controlled to be 56mN / m.
[0132] Step 4: Preparation of composite adhesive solution. The composite adhesive solution is prepared according to the following mass percentages: modified epoxy resin 54.5%, cyanate ester resin 18.2%, nano alumina 4.5%, flame retardant synergist 2.7%, silane coupling agent 0.5%, with the remainder being solvent to achieve the coating viscosity. The solvent is selected from water, alcohol ethers, or ketones, preferably deionized water, accounting for 19.6% of the total mass of the adhesive solution.
[0133] Step 5: Coating and laminating. Apply the laminating adhesive to the corona-treated film surface at a coating weight of 15 g / m². 2 It is then laminated with flame-retardant nonwoven fabric by roller pressing at a pressure of 0.8 MPa.
[0134] Step 6: Hot pressing. Place the composite blank in a hot press and cure it in stages: first stage 100℃ / 1h, second stage 140℃ / 2h, third stage 180℃ / 3h, with the pressure maintained at 10MPa throughout.
[0135] The plasma treatment in step one was carried out under a nitrogen atmosphere with a gas flow rate of 50 L / min. After treatment, a nanoscale pit structure was formed on the surface of the nonwoven fabric, with a pit depth of 200 nm and a density of 10. 6 pcs / cm 2 .
[0136] The flame retardant liquid in step two is composed of the following components by mass percentage:
[0137] Ammonium polyphosphate: 25%;
[0138] Melamine cyanurate: 15%;
[0139] Zinc borate: 8%;
[0140] Dispersant, polyvinyl butyral: 0.5%;
[0141] The remaining volume is 51.5% deionized water;
[0142] Flame retardant liquids must meet the following requirements: deionized water conductivity ≤ 0.1 μS / cm, total metal ion content ≤ 50 ppb;
[0143] The pH of the flame retardant liquid was adjusted to 7.5, and the viscosity was controlled to 50 mPa·s.
[0144] The modified epoxy resin in step four is a mixture of bisphenol A type epoxy resin and phosphorus-containing epoxy resin, with a mixing mass ratio of 5:5 and an epoxy equivalent of 220 g / eq.
[0145] Nano-alumina is a γ phase Particle size 50nm, specific surface area 150m² 2 / g, surface modified with silane coupling agent KH-550.
[0146] The flame retardant synergist in step four is prepared by the following method:
[0147] Waste ceramic powder was ball-milled to a particle size of 5μm and then mixed with aluminum hydroxide at a mass ratio of 3:1.
[0148] Placed in a plasma reactor, argon gas is introduced to achieve a pressure of [insert pressure here]. Pa, processed at 500W power for 30 minutes;
[0149] The treated powder was immersed in 5% silica sol for 10 minutes and then dried to obtain a coated flame retardant synergist.
[0150] Step four, the preparation of the composite adhesive solution, specifically includes:
[0151] The modified epoxy resin and cyanate ester resin were stirred and mixed at 400 r / min for 40 min at 60℃.
[0152] Add silane coupling agent and nano-alumina, and ultrasonically disperse at 1200W for 30 minutes;
[0153] Add flame retardant synergist, heat to 80℃ and continue stirring for 60 minutes;
[0154] Cool the temperature down to below 40℃, add 3 parts of the curing agent dicyandiamide and mix well;
[0155] Add the selected solvent and adjust the viscosity of the adhesive to 50 mPa·s at 25°C.
[0156] Step five, roll lamination, uses a three-roll coating machine, wherein:
[0157] The gap between the coating roller and the metering roller is 0.15mm, the temperature of the composite pressure roller is set to 70℃, the composite speed is 5m / min, and the composite material is immediately placed in an 80℃ hot air zone for pre-curing for 3min.
[0158] Step six, hot pressing, employs a segmented pressure relief technique:
[0159] The pressure was released to 3 MPa 10 minutes before the end of the first stage of heating and held for 10 minutes.
[0160] 15 minutes before the end of the second stage, the pressure was released to 2 MPa and held for 15 minutes.
[0161] 20 minutes before the end of the third stage, the pressure was released to atmospheric pressure and maintained until the end.
[0162] A post-processing step is added after hot pressing in step six:
[0163] The molding material was placed in a vacuum oven and treated at 140℃ for 4 hours, with a vacuum degree ≤ Pa;
[0164] Immediately after treatment, immerse the sample in a coolant containing 0.5% fluorocarbon surfactant to cool it rapidly to room temperature.
[0165] An ultrasonic vibration device is added between the coating roller and the metering roller. This device satisfies the following requirements:
[0166] The vibration frequency was 40 kHz, the amplitude was 15 μm, and the vibration direction was at a 90° angle to the coating direction. The ultrasonic vibration was continuously applied during the coating process, and the vibration energy density was controlled at 2.0 J / cm². 2 ·s.
[0167] Comparative Example 1 differs from Example 1 in that: no plasma hydrophilization treatment was performed, and the original polyester nonwoven fabric was directly used for subsequent flame retardant impregnation.
[0168] Comparative Example 2 differs from Example 1 in that no flame retardant synergist was added during the preparation of the composite adhesive; it only contains modified epoxy resin, cyanate ester resin, nano-alumina, silane coupling agent, and solvent.
[0169] Comparative Example 3 differs from Example 1 in that the ultrasonic vibration device was not used in the roll forming process, and the coating process was completed solely by mechanical roll forming.
[0170] Comparative Example 4 differs from Example 1 in that: after hot pressing, no vacuum post-treatment or rapid cooling process was performed, and the material was directly cooled to room temperature naturally after hot pressing.
[0171] The performance of the nonwoven fabric-film composite insulating materials prepared in Examples 1-3 and Comparative Examples 1-4 was tested. The test items and test methods are as follows:
[0172] Dielectric strength test: Under an environment of 23±2℃ and 50±5% relative humidity, a withstand voltage tester is used to uniformly increase the voltage at a rate of 500V / s until the material breaks down. The breakdown voltage value is recorded and the dielectric strength is calculated.
[0173] For thermal stability testing, the sample was placed in a thermogravimetric analyzer and heated to 300℃ at a rate of 10℃ / min under a nitrogen atmosphere. The percentage of thermal weight loss of the material during the isothermal stage at 180℃ was recorded. Simultaneously, the storage modulus decay rate at 180℃ was measured using a dynamic thermomechanical analyzer (DMA).
[0174] Peel strength testing was conducted using a universal testing machine at a peel speed of 100 mm / min and a peel angle of 180° to measure the peel force at the interface between the nonwoven fabric and the film composite. The samples were pretreated at 23°C for 24 hours before the test.
[0175] For flame retardant performance testing, a nitrogen-oxygen mixture was used in an oxygen index meter. The initial oxygen concentration was 21%. The oxygen concentration was adjusted until the sample could burn continuously for 3 minutes or the damaged length reached 50 mm. The limiting oxygen index (LOI) was then recorded.
[0176] The test data of the nonwoven fabric-film composite insulation materials prepared in Examples 1-3 and Comparative Examples 1-4 are recorded in the table below:
[0177]
[0178] By comparing and analyzing the data in the table, it can be seen that the nonwoven fabric-film composite insulation materials prepared by the process in Examples 1-3 have performance advantages compared with Comparative Examples 1-4. This indicates that by synergistically controlling the temperature field and pressure field during the hot pressing stage to dynamically match the deformation behavior of the substrate, the interfacial microbubble defects caused by uneven local temperature distribution and pressure fluctuations are eliminated, achieving molecular-level fusion of the nonwoven fabric and film interface and improving the interlayer bonding strength. At the same time, by utilizing the coating structure of the flame retardant synergist and the pH control of the adhesive, the abnormal migration of flame retardant molecules during the hot pressing process is dynamically suppressed, ensuring the long-term stability of the dielectric properties of the composite system and avoiding the problem of insulation performance degradation caused by flame retardant concentration imbalance. By leveraging the synergistic surface activation effect of plasma treatment and corona treatment, a nanoscale anchoring structure is constructed on the nonwoven fabric surface, enhancing the surface polarity of the film. This allows the composite adhesive to achieve both chemical bonding and mechanical interlocking at the substrate interface. Through surface modification of nanoparticles and directional ultrasonic dispersion technology, the arrangement of the reinforcing phase in three-dimensional space is controlled, eliminating stress concentration caused by particle aggregation, blocking crack propagation paths at high temperatures, and improving the reliability of the composite insulation material under extreme conditions. The coupling effect of segmented pressure-relief hot pressing technology and vacuum post-treatment processes releases residual interfacial stress in stages and eliminates micropores, allowing the adhesive layer to form a dense interpenetrating network structure during curing. Combined with the resin micro-phase transformation induced by rapid cooling, the mechanical interlocking and chemical cross-linking density of the composite interface are strengthened, achieving a fully integrated nonwoven fabric-film-adhesive layer sandwich structure. This ensures the material simultaneously possesses the comprehensive performance advantages of high insulation, toughness, and heat resistance.
[0179] By comparing and analyzing the test data in the table above, it can be seen that the nonwoven fabric-film composite insulation material prepared by the hot pressing molding process of the present invention not only has excellent electrical insulation, high flame retardancy and stable thermomechanical properties, but also shows that the hot pressing molding process of the nonwoven fabric-film composite insulation material provided by the present invention has a broader market prospect in the field of new energy equipment insulation and is more suitable for large-scale promotion.
[0180] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0181] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A process for thermoforming a nonwoven-film composite insulation material, characterized in that: Comprising the following steps: Step one: substrate pretreatment, select polyester non-woven fabric and polyimide film, wherein the non-woven fabric weight is 30-50g / m 2 , thickness 0.1-0.3mm, film thickness is 12-25μm, the non-woven fabric is treated by plasma hydrophilization, treatment power is 300-800W, time is 30-90s; Step two: flame-retardant impregnation, after pretreatment, the non-woven fabric is immersed in the flame-retardant liquid, the impregnation temperature is 40-60℃, the time is 5-15min, and after taking out, it is dried at 80-100℃; Step three: film surface treatment, the polyimide film is treated on one side by corona treatment, and the surface tension is controlled to be 50-56mN / m; Step four: preparation of composite glue solution, the composite glue solution is prepared according to mass percentage: modified epoxy resin 36.4%-54.5%, cyanate ester resin 18.2%-27.3%, nano-alumina 4.5%-9.1%, flame-retardant synergist 2.7%-7.3%, silane coupling agent 0.5%-1.8%, and the rest is solvent to achieve the coating viscosity, the solvent is selected from water, alcohol ether or ketone, accounting for 15-20% of the total mass of the glue solution; Step five: coating and compounding, coating the compounding glue on the surface of the film after corona treatment, coating amount 8-15 g / m 2 , then compounding with the non-woven fabric treated by flame retardant through roller compounding, roller compounding pressure 0.3-0.8 MPa; Step six: hot pressing, the composite blank is placed in a hot press, and the temperature is raised in stages: the first stage is 80-100℃ / 0.5-1h, the second stage is 120-140℃ / 1-2h, and the third stage is 160-180℃ / 2-3h, and the pressure is maintained at 5-10MPa throughout the process.
2. The nonwoven-film composite insulation thermoforming process of claim 1, wherein: The plasma treatment of step one is carried out under nitrogen atmosphere, gas flow 20-50 L / min, after treatment, nano-scale pit structure is formed on the surface of the non-woven fabric, pit depth 50-200 nm, density 10 5 -10 6 / cm 2 .
3. The nonwoven-film composite insulation thermoforming process of claim 1, wherein: The flame-retardant liquid of step two is composed of the following components according to mass percentage Ammonium polyphosphate: 15-25%; Melamine cyanurate: 8-15%; Zinc borate: 3-8%; Dispersing agent, polyvinyl butyral: 0.5-1.5%; The rest is deionized water 50.5-73.5%; The flame-retardant liquid needs to meet: deionized water conductivity ≤0.1μS / cm, total metal ion content ≤50ppb; The pH value of the flame-retardant liquid is adjusted to 6.5-7.5, and the viscosity is controlled to be 25-50mPa·s. The modified epoxy resin of step four is a mixture of bisphenol A type epoxy resin and phosphorus-containing epoxy resin, with a mixing mass ratio of 7:3-5:5, and an epoxy equivalent weight of 180-220g / eq; 4. The nonwoven-film composite insulation thermoforming process of claim 1, wherein: The flame-retardant synergist of step four is prepared by the following method: The nano-alumina is in a gamma phase , a particle size of 20-50 nm, a specific surface area of 80-150 m 2 / g, and is surface modified by a silane coupling agent KH-550.
5. The nonwoven-film composite insulation thermoforming process of claim 1, wherein: The waste ceramic powder is ball milled to a particle size of 1-5μm, and mixed with aluminum hydroxide according to a mass ratio of 3:1; The treated powder is immersed in a 5% mass fraction of silica sol for 10min, and dried to obtain a coated flame-retardant synergist. The samples were placed in a plasma reactor and treated with argon at a pressure of 0.1 Pa for 10-30 min at a power of 200-500 W. Pa, at a pressure of 0.1 Pa for 10-30 min at a power of 200-500 W. The preparation of the composite glue solution of step four specifically includes:
6. The nonwoven-film composite insulation thermoforming process of claim 1, wherein: Mix the modified epoxy resin and cyanate ester resin at 50-60℃ with stirring at 200-400r / min for 20-40min; Add silane coupling agent and nano-alumina, and ultrasonic dispersion at a power of 800-1200W for 15-30min; Add the flame-retardant synergist, heat to 70-80℃, and continue stirring for 30-60min; Cool down to below 40℃, add 1-3 parts of curing agent dicyandiamide and mix evenly; Add the selected solvent, adjust the glue solution viscosity to 25-50mPa·s at 25℃. The roll pressing of step five uses a three-roll coater, in which:
7. The nonwoven-film composite insulation thermoforming process of claim 1, wherein: The gap between the coating roll and the metering roll is 0.05-0.15mm, the composite pressure roll temperature is set to 50-70℃, the composite speed is 2-5m / min, and the material after compounding immediately enters the 60-80℃ hot air zone for pre-curing for 1-3min. The hot pressing of step six uses a segmented pressure relief technology:
8. The nonwoven-film composite insulation thermoforming process of claim 1, wherein: 10 minutes before the end of the first stage, pressure is released to 2-3 MPa and maintained for 10 minutes; 15 minutes before the end of the second stage, pressure is released to 1-2 MPa and maintained for 15 minutes; 20 minutes before the end of the third stage, pressure is released to normal pressure and maintained until the end.
9. The nonwoven-film composite insulation thermoforming process of claim 1, wherein: After the hot-pressing forming in step six, a post-treatment process is added: The molding material is placed in a vacuum oven and treated at 120-140°C for 2-4 h at a vacuum of < 0.1 Pa. Pa; Immediately after the treatment, quenching to room temperature is performed by immersing in a cooling liquid containing 0.5% fluorocarbon surfactant.
10. The nonwoven-film composite insulation thermoforming process of claim 7, wherein: An ultrasonic vibration device is added between the coating roller and the metering roller, which satisfies: The vibration frequency is 20-40 kHz, the amplitude is 5-15 μm, the vibration direction is 45°-90° to the coating direction, the ultrasonic vibration is continuously applied during the coating process, and the vibration energy density is controlled at 0.5-2.0 J / cm 2 ·s.
Citation Information
Patent Citations
High-performance flame-retardant antistatic powder coating and preparation method thereof
CN114250027A
Laminate of heat-resistant film and polyimide resin, and its production
JP2000135765A